The Contribution of Photon, Z Boson, Higgs, Radion and Unparticle to the Process in Randall-Sundrum model - Mai Dung, Le; Thi Le Thuy, Dao (VNU Journal of Science: Mathematics - Physics, 2023)
T he process is studied from unparticle physics perspective in Randall-Sundrum model. We calculated and evaluated the cross sections independently for photon ( γ ), Z boson ( Z ) , vector unparticle (U μ ), Higgs ( h ), radion ( ), scalar unparticle ( U ) exchange. Numerical calculations showed that the contribution of unparticle exchange dominates in a very high energy region. While γ and Z contribute mainly in the lower region, h and contribution is negligible in comparison with the other exchanges. The results are plotted in the energy ranges available in the present designs of accelerators and near future high energy frontier muon colliders as shown by International Muon Collider Collaboration articles. Keywords: M uon production, unparticle physics, collisions, muon colliders, Randall-Sundrum model.